Historique et variations de la restauration des œuvres de Nicolas Schöffer - Éléonore de Lavandeyra Schöffer (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This text is the transcription of Éléonore de Lavandeyra Schöffer’s talk at the first study day held on November 3, 2016, at the Villa des Arts (Paris). It goes along with the video of the presentation. After a short introduction of the artworks and the studio of Nicolas Schöffer to the audience, Éléonore Schöffer presents her experiences and reflections related to the artworks conservation over time. She reviews the artist’s different categories of works and some keys to understand their evolution.